2010
DOI: 10.1007/s10237-010-0233-7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of postnatal collagen reorientation to depth-dependent mechanical properties of articular cartilage

Abstract: The collagen fibril network is an important factor for the depth-dependent mechanical behaviour of adult articular cartilage (AC). Recent studies show that collagen orientation is parallel to the articular surface throughout the tissue depth in perinatal animals, and that the collagen orientations transform to a depth-dependent arcade-like structure in adult animals. Current understanding on the mechanobiology of postnatal AC development is incomplete. In the current paper, we investigate the contribution of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Dedicated finite element models can be an aid for a functional analysis of these effects, e.g. [10,18]. In our previous study [23] we found that differences during development had disappeared in the last sample point (72 weeks).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Dedicated finite element models can be an aid for a functional analysis of these effects, e.g. [10,18]. In our previous study [23] we found that differences during development had disappeared in the last sample point (72 weeks).…”
Section: Discussionmentioning
confidence: 98%
“…[10,29,53]. We performed such a functional analysis [18] with our earlier data on collagen orientation remodelling [23]. In that functional analysis [18] we found a marked increase in AC stiffness near the bone, but not at the articular surface.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations